Territories and Trajectories : Cultures in Circulation - Sorensen, Diana (Book collections on Project MUSE., 2018)
The contributors to Territories and Trajectories propose a model of cultural production and transmission based on the global diffusion, circulation, and exchange of people, things, and ideas across time and space. This model eschews a static, geographically bounded notion of cultural origins and authenticity, privileging instead a mobility of culture that shapes and is shaped by geographic spaces. Reading a diverse array of texts and objects, from Ethiopian song and ancient Chinese travel writing to Japanese literature and aerial and nautical images of the Indian Ocean, the contributors decenter national borders to examine global flows of culture and the relationship between thinking at transnational and local scales. Throughout, they make a case for methods of inquiry that encourage innovative understandings of borders, oceans, and territories and that transgress disciplinary divides.